Biomass and root development response of lulo (Solanum quitoensevar. septentrionale) plants to shading and waterlogging - Cardona, William Andrés Andres; Bautista-Montealegre, Luis Gabriel; Flórez-Velasco, Nixon; Fischer, Gerhard (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2016)
Climate change and its variability increase rainy periods, generating flooding and waterlogging, which affect the physiological development of cultivated species. In lulo, although growth under shade is recommended, the effect of stress due to waterlogging was studied under conditions of partial shading in greenhouse. Young lulo plants were planted in 5 L plastic pots with soil and sand quartzite at a ratio of 1: 1 v/v as substrate. The effect of 65% shading and no shading during four periods of waterlogging, 0, 3, 6 and 9 days, and a recovery period of 9 days each on the development of plant biomass and roots was determined. The shading decreased biomass accumulation in all of the vegetative organs, especially the leaves (-22.7%). No interactions between the shading and waterlogging were measured. The root system proved to be the organ most affected by the periods of increased waterlogging (over 6 and 9 days), with reductions in the diameter of the root collar, length of taproot, volume and dry weight of roots, while; as a consequence, the shoot/root ratio of the biomass increased due to rhizosphere oxygen deprivation. During the recovery period of 9 days, the negative effect of the waterlogging persisted and was further aggravated for the volume and root length variables.